The interplay between autophagy and ferroptosis presents a novel conceptual therapeutic framework for neuroendocrine prostate cancer - Youzhi Wang; Ning Wu; Junbo Li; Jiaming Liang; Diansheng Zhou; Qian Cao; Xuesong Li; Ning Jiang (Elsevier, 2024)
In American men, the incidence of prostate cancer (PC) is the highest among all types of cancer, making it the second leading cause of mortality associated with cancer. For advanced or metastatic PC, antiandrogen therapies are standard treatment options. The administration of these treatments unfortunately carries the potential risk of inducing neuroendocrine prostate cancer (NEPC). Neuroendocrine differentiation (NED) serves as a crucial indicator of prostate cancer development, encompassing various factors such as phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR), Yes-associated protein 1 (YAP1), AMP-activated protein kinase (AMPK), miRNA. The processes of autophagy and ferroptosis (an iron-dependent form of programmed cell death) play pivotal roles in the regulation of various types of cancers. Clinical trials and preclinical investigations have been conducted on many signaling pathways during the development of NEPC, with the deepening of research, autophagy and ferroptosis appear to be the potential target for regulating NEPC. Due to the dual nature of autophagy and ferroptosis in cancer, gaining a deeper understanding of the developmental programs associated with achieving autophagy and ferroptosis may enhance risk stratification and treatment efficacy for patients with NEPC.